LEGAL RESPONSIBILITY OF CIVIL SERVANTS OF THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article suggests ways to solve these problems and increase the effectiveness of the mechanism for bringing civil servants to legal responsibility. With the revision of the existing system of evaluating the effectiveness of a civil servant in public authorities, in order to establish a balance between his encouragement and punishment on an analytical basis, the possibility of solving these problems with prevention is proposed. The priorities of the proposed problem are analyzed, some expansion of the introduction of digital mechanisms and the strengthening of the role of public control institutions, and appropriate recommendations are given. Also in the article, the author supports his arguments with examples of scientific hypotheses of a number of foreign and domestic scientists.
Keywords: -